Calcium channel TRPV6 promotes breast cancer metastasis by NFATC2IP. (28th October 2021) - Xu, Xiang; Li, Na; Wang, Yugang; Yu, Jinming; Mi, Jun
Abstract: Calcium channel TRPV6 upregulation is associated with poor prognosis of breast cancer by promoting invasion and metastasis, and TRPV6 is a potential target for breast cancer therapy. However, the mechanism by which TRPV6 promotes breast metastasis remains unclear. Here, we report that TRPV6 expression is upregulated in metastatic breast cancers and that TRPV6 overexpression or upregulation accelerates primary breast cancer cell migration. In contrast, TRPV6 suppression decreases cell migration. Mechanistically, TRPV6 activates NFATC2 by increasing NFATC2IP phosphorylation at Ser204, and CDK5 is a candidate kinase that may perform this phosphorylation. Consequently, activated NFATC2 increases breast cancer metastasis by upregulating ADAMTS6 expression. These observations suggest that TRPV6 increases NFATC2 transcriptional activity by increasing NFATC2IP phosphorylation, which consequently upregulates ADAMTS6 expression to promote breast cancer metastasis. Highlights: The expression of TRPV6 is upregulated in metastatic breast cancers. TRPV6 activates NFATC2 by increasing NFATC2IP phosphorylation. TRPV6 upregulates ADAMTS6 by NFATC2. TRPV6 promotes breast cancer cell metastasis by upregulating ADAMTS6.